Pemberdayaan Masyarakat dalam Pembuatan Nugget Ikan Sebagai Diversifikasi Olahan Ikan untuk Meningkatkan Pendapatan Mitra - Sitti Sabariyah; Muh. Jufri; Spetriani Spetriani; Marjun Marjun; Asrawaty Asrawaty (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2023)
Salubomba Village, Donggala Regency is a coastal village whose residents are mostly fishermen and farmers. Fish caught by fishermen are still sold in raw form. The training activity aims to train the Salubomba Village community who are members of partner groups to process fish so that it has relatively high economic added value. In addition, encouraging the partner group to start and own a fish nugget business. The implementation method starts from the discussion stage and preparation of training between the team and partner groups. The service was then continued with technical training in the form of fish nugget processing demonstrations and non-technical training in the form of presenting material on product marketing strategies through online media, recording cash bookkeeping and institutional strengthening. The results of the activities assessed have increased the knowledge of partner groups regarding good fish nugget processing. In addition, the partner group also offered to develop the potential of marine fishery products in Salubomba Village. This can be seen from the enthusiasm of the partner groups in participating in all service activities. Post-training assistance is also carried out, especially in relation to business bookkeeping and the process of obtaining product distribution permits or P-IRT. Keywords: community service, processed fish, fish nuggets, salubomba village